Herpetic tracheitis in association with rituximab therapy. Issue 4 (5th May 2016) - Thong, Lorraine; Plant, Barry J; McCarthy, Julie; Murphy, Desmond M
Abstract: A 58‐year old lady under active follow‐up with the respiratory services at our institution for bronchiectasis secondary to hypogammaglobulinaemia presented with hoarseness and haemoptysis. She was also receiving rituximab maintenance therapy for follicular lymphoma. Bronchoscopy demonstrated vesicular lesions on her vocal cords and trachea, confirmed as herpes simplex virus (HSV) on cytological analysis of brushings. She responded well to intravenous valacyclovir. Rituximab is increasingly utilised in the treatment of haematological and auto‐immune disorders. This case highlights the potential of this drug to potentiate susceptibility to infection in an already immunocompromised individual. Abstract : We present a case of herpetic tracheitis in a patient on rituximab therapy for follicular lymphoma. Bronchoscopy demonstrated vesicular lesions on her vocal cords and trachea, confirmed as Herpes Simplex Virus (HSV) on cytological analysis of brushings. Rituximab is increasingly utilised in the treatment of haematological and auto‐immune disorders and this case highlights the potential of this drug to potentiate susceptibility to infection in an already immunocompromised individual.